Pengaruh Model Problem Based Learning Dan Motivasi Belajar Terhadap Kemampuan Menganalisis Unsur Intrinsik Cerpen Peserta Didik Fase F SMAN 7 Mandau-Duri - Yasmanelly, Yasmanelly; Fikri, Hasnul; Syofiani, Syofiani (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to analyze the ability of 11th-grade students (Phase F) at SMA Negeri 7 Mandau-Duri to analyze intrinsic elements of short stories through the implementation of the Problem-Based Learning (PBL) model and the conventional learning model, viewed from learning motivation and the interaction between learning models and learning motivation. This research employs a quantitative approach with a quasi-experimental method. The research subjects consist of 30 11th-grade students. Data on the ability to analyze intrinsic elements of short stories were collected through tests, while learning motivation data were obtained through questionnaires. Data analysis was conducted using descriptive and inferential statistics. The results indicate that the ability of students learning with the PBL model to analyze intrinsic elements of short stories is higher compared to those learning with the conventional model. Learning motivation serves as a supporting factor in enhancing short story analysis skills, although its influence is relatively smaller than that of the learning model. Grouping of high and low learning motivation was performed based on the average motivation score to maintain analysis validity. Additionally, there is a positive interaction between the PBL model and learning motivation in influencing the ability to analyze intrinsic elements of short stories. Based on these findings, it can be concluded that the application of the Problem-Based Learning model, supported by students' learning motivation, effectively improves the ability to analyze intrinsic elements of short stories. The PBL model is recommended for implementation in high school literature instruction.